Clinical Profile and Risk Factors for Severe Disease in 402 Children Hospitalized with SARS-CoV-2 from India: Collaborative Indian Pediatric COVID Study Group. (21st June 2021) - Jat, Kana Ram; Sankar, Jhuma; Das, Rashmi Ranjan; Ratageri, Vinod H; Choudhary, Bharat; Bhat, Javeed Iqbal; Mishra, Baijayantimala; ,; Bhatnagar, Sushma; Behera, Bijayini; Charoo, Bashir Ahmad; Goyal, Jagdish P; et al.
Abstract: Introduction: There is a lack of large multicentric studies in children with COVID-19 from developing countries. We aimed to describe the clinical profile and risk factors for severe disease in children hospitalized with COVID-19 from India. Methods: In this multicentric retrospective study, we retrieved data related to demographic details, clinical features, including the severity of disease, laboratory investigations and outcome. Results: We included 402 children with a median (IQR) age of 7 (2–11) years. Fever was the most common symptom, present in 38.2% of children. About 44% had underlying comorbidity. The majority were asymptomatic (144, 35.8%) or mildly symptomatic (219, 54.5%). There were 39 (9.7%) moderate-severe cases and 13 (3.2%) deaths. The laboratory abnormalities included lymphopenia 25.4%, thrombocytopenia 22.1%, transaminitis 26.4%, low total serum protein 34.7%, low serum albumin 37.9% and low alkaline phosphatase 40%. Out of those who were tested, raised inflammatory markers were ferritin 58.9% (56/95), c-reactive protein 33.3% (41/123), procalcitonin 53.5% (46/86) and interleukin-6 (IL-6) 76%. The presence of fever, rash, vomiting, underlying comorbidity, increased total leucocyte count, thrombocytopenia, high urea, low total serum protein and raised c-reactive protein was factors associated with moderate to severe disease. Conclusion: Fever was the commonest symptom. We identified additional laboratory abnormalities, namely lymphopenia, low total serum protein and albumin and low alkaline phosphatase. The majority of the children were asymptomatic or mildly symptomatic. We found high urea and low total serum protein as risk factors for moderate to severe disease for the first time.